Antitumor activity of antisense oligonucleotide p45Skp2 in soft palate carcinoma cell squamous in vitro - Supriatno Supriatno; Sartari Entin Yuletnawati; Iwa Sutardjo Rus Sudarso (Universitas Airlangga, 2013)
Background: Human soft palate cancers are characterized by a high degree of local invasion and metastasis to the regional lymph nodes. Treatment options for this cancer are limited. However, a new strategy for refractory cancer, gene therapy is watched with keen interest. p45Skp2 gene as a tumor promoter gene is one of target of the oral cancer therapy. To inhibit the activity of p45Skp2 gene is carried-out the genetic engineering via antisense technique. Purpose: To examine the antitumor activity of p45Skp2 antisense (p45Skp2 AS) gene therapy in human soft palate [Hamakawa-Inoue (HI)] cancer cells. Methods: Pure laboratory experimental study with post test only control group design was conducted as a research design. To investigate the apoptosis induction of p45Skp2 AStransfected cell was evaluated by colorimetric caspase-3 assay and Flow cytometry. Furthermore, to detect the suppression of in vitro HI cell invasion and cell growth of p45Skp2 AS-treatment cell was examined by Boyden chamber kit and MTT assay, respectively. Results: The cell number of p45Skp2 AS-treated HI cell was significant decreased when compared with that of p45Skp2 sense (p45Skp2 S) cells (p<0.05). p45Skp2 AS-treated cell induced apoptosis characterized by an increase in the early and late apoptosis, and activation of caspase-3 (p<0.05). Therefore, suppression of HI cell invasion and cell growth were markedly increased by p45Skp2 AS treatment (p<0.05).